2018
DOI: 10.1007/s00441-018-2793-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of trans-membrane serine protease 3 (TMPRSS3) in the human organ of Corti

Abstract: TMPRSS3 (Trans-membrane Serine Protease 3) is a type II trans-membrane serine protease that has proteolytic activity essential for hearing. Mutations in the gene cause non-syndromic autosomal recessive deafness (DFNB8/10) in humans. Knowledge about its cellular distribution in the human inner ear may increase our understanding of its physiological role and involvement in deafness, ultimately leading to therapeutic interventions. In this study, we used super-resolution structured illumination microscopy for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Table 1 shows the antibodies used in the present study. The immunohistochemistry procedures performed on the sections have been described in previous publications (1921). Briefly, the slide-mounted sections were incubated with an antibody solution under a humidified atmosphere at 4°C for 20 h. After rinsing with PBS three times for 5 min each, the sections were incubated with secondary antibodies conjugated to Alexa Fluor 488, 555, and 647 (Molecular Probes, Carlsbad, CA, USA), counter-stained with the nuclear stain 4′,6-diamidino-2-phenylindole dihydro-chloride (DAPI; Thermo Fisher Scientific, Waltham, MA, USA) for 5–7 min, rinsed with PBS (3 × 5 min), mounted with ProLong® Gold Antifade Mountant (Thermo Fisher Scientific), and covered with the specified cover glass required for optically matching the SIM objectives.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the antibodies used in the present study. The immunohistochemistry procedures performed on the sections have been described in previous publications (1921). Briefly, the slide-mounted sections were incubated with an antibody solution under a humidified atmosphere at 4°C for 20 h. After rinsing with PBS three times for 5 min each, the sections were incubated with secondary antibodies conjugated to Alexa Fluor 488, 555, and 647 (Molecular Probes, Carlsbad, CA, USA), counter-stained with the nuclear stain 4′,6-diamidino-2-phenylindole dihydro-chloride (DAPI; Thermo Fisher Scientific, Waltham, MA, USA) for 5–7 min, rinsed with PBS (3 × 5 min), mounted with ProLong® Gold Antifade Mountant (Thermo Fisher Scientific), and covered with the specified cover glass required for optically matching the SIM objectives.…”
Section: Methodsmentioning
confidence: 99%
“…The function of the protein encoded by TMPRSS3 , transmembrane serine protease 3, is unknown. However, multiple studies have shown the protein to be expressed in inner and outer hair cells as well as the spiral ganglion, including in dissected human temporal bones . A recent study showed that TMPRSS3 is expressed highly in type II spiral ganglion neurons in mice .…”
Section: Genes With Possible Effects On the Auditory Synapse Or Spiramentioning
confidence: 99%
“…In humans, TEM shows a dense meshwork associated with cell junctional complexes at the plasma membrane referred to as surfoskelosomes [13]. These are located in the pillar heads and foot (basal bodies) that contain organized actin and are closely associated with microtubules [16]. Deiters' cells also express organized actin in basal bodies.…”
Section: Cell Contractilitymentioning
confidence: 99%
“…An intriguing association was found between actin and the enzyme TMPRSS3, a type II trans-membrane serine protease , [16]. Several mutations in the TMPRSS3 gene on chromosome 21q22.3 cause autosomal recessive non-syndromic deafness (DFNB8/10) with varied phenotypic expression [23,24].…”
Section: Cx30 For a 'Cochlear Symphony'mentioning
confidence: 99%